Eco-friendly recovery of base and precious metals from waste printed circuit boards by step-wise glycine leaching: Process optimization, kinetics modeling, and comparative life cycle assessment. (20th February 2023) - Rezaee, Mohammad; Saneie, Roozbeh; Mohammadzadeh, Amirhossein; Abdollahi, Hadi; Kordloo, Mehrdad; Rezaee, Ali; Vahidi, Ehsan
Abstract: Glycine as a green alternative to cyanide for gold leaching is a promising reagent to put a curb on the environmental footprints of conventional hydrometallurgical processes. This work was designed to investigate the step-wise glycine leaching of the base and precious metals from waste printed circuit boards (WPCBs) as one of the most dominant and problematic e-wastes in today's world. Using response surface methodology, selective copper extraction reached 99.96% recovery at the optimum condition of 0.5 M glycine, 1% v/v H2 O2, 20 g/l pulp density, and ambient temperature. Copper sulfide was then recovered from the leach solution via precipitation by sodium hydrosulfide. Gold leaching in the glycine + permanganate system was thoroughly studied with an emphasis on the process's kinetics mechanisms. It was revealed that gold leaching in the glycine and permanganate system starts with a rapid phase followed by a slower chemically controlled phase. At the optimum condition of 4 g/l glycine, 2 g/l potassium permanganate, and room temperature, 96.17% of the gold was selectively extracted. By using 3 g/L activated carbon, about 100% of the gold was separated from the leach solution. Comparative life cycle assessment revealed that in the proposed process, the main contributor to most of the environmental impact categories is glycine. Replacing the first step of glycine copper leaching with nitric acid can substantially reduce the environmental footprints of the process to a lower level than many other proposed recycling routes. Graphical abstract: Image 1 Highlights: 99.96% copper was selectively recovered at ambient temperature with glycine + H2 O2 . 96.17% gold from the first step's residue was recovered using glycine + permanganate. About 100% of the gold was recovered using 3 g/l activated carbon. The final residue was categorized as environmentally safe, based on the TCLP test. A comprehensive comparative LCA based on six hydrometallurgical routes was conducted.